Water vapor barrier composition and water vapor barrier laminate

A styrene-based thermoplastic resin and hydrocarbon wax composition forms a dense, crystalline structure on substrates, addressing durability and process limitations of existing wax-based barrier methods, achieving superior water vapor barrier performance.

CN119256046APending Publication Date: 2025-01-03아티엔스가부시키가이샤 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380038621.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-13
Filing Date
2023-05-11
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing methods for imparting water vapor barrier properties to substrates, such as plastic films and papers, face challenges in durability and softness when using wax alone, and require specialized coating devices for polyolefin resin and wax compositions, limiting process flexibility.

Method used

A water vapor barrier composition comprising a styrene-based thermoplastic resin and hydrocarbon wax, which forms a dense, crystalline structure upon heating, providing enhanced water vapor barrier properties without the need for vacuum processes.

Benefits of technology

The composition allows for the formation of a high-performance water vapor barrier layer on substrates by coating, exceeding the properties of conventional organic materials, with improved durability and flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119372950000241
    Figure BDA0005119372950000241
  • Figure BDA0005119372950000251
    Figure BDA0005119372950000251
  • Figure BDA0005119372950000281
    Figure BDA0005119372950000281
Patent Text Reader

Abstract

Embodiments of the present invention relate to a water vapor barrier composition comprising a styrene-based thermoplastic resin (A) and a hydrocarbon-based wax (B), and a water vapor barrier laminate using the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to a water vapor barrier composition capable of expressing high water vapor barrier properties, and a laminate using the water vapor barrier composition. Background Art

[0002] In recent years, as food loss has become a global problem, the long-term maintenance of food quality and the prevention of waste have become issues. Among them, the contents used in food packaging are often degraded by gases such as oxygen and water vapor in the atmosphere, so there is a demand for the development of raw materials with high gas barrier properties or transparency like glass.

[0003] In order to impart water vapor barrier properties, inorganic materials including metals such as aluminum or aluminum oxide or silicon dioxide are generally used in the barrier layer. In order to achieve high water vapor barrier properties, the method of forming these inorganic layers on plastic film substrates by vacuum processes such as chemical vapor deposition (CVD) or evaporation has gradually become the mainstream, but in the structure including the inorganic layer, there are problems such as tolerance caused by defects such as cracks. In order to solve these problems, multilayer structures that combine organic layers and inorganic layers that effectively utilize the flexibility of organic materials have also been studied, but considering recyclability, it is preferably made into a single-layer structure, and in order to achieve it, it is preferred that the organic layer has a high water vapor barrier property.

[0004] It is believed that improving the water vapor barrier property of the organic layer will not only contribute to solving the food loss problem described above, but also improve the reliability of a wide range of existing products such as peripheral components of solar cells, medical products, and food packaging. In addition, if a high water vapor barrier property can be imparted to a substrate by simple coating, it will be a great manufacturing advantage compared to the method of forming an inorganic layer by a vacuum process.

[0005] Several methods of using organic materials to impart water vapor barrier properties have been considered, among which, when wax is used for the barrier layer, high water vapor barrier properties have been reported (Non-Patent Document 1). However, the content disclosed in Non-Patent Document 1 is limited to the case where wax is used alone, and does not consider the durability and softness when the coating is appropriate or the water vapor barrier layer is formed. On the other hand, as a material having water vapor barrier properties, a composition comprising a combination of polyolefin resin and wax is known. For example, Patent Document 1 discloses a hot melt type composition of polyolefin resin and wax for moisture-proof paper. However, the coating of the substrate needs to be heated above the melting point, so a special coating device is required, which greatly restricts the process.

[0006] Prior art literature

[0007] Non-patent literature

[0008] Non-patent literature 1: Critical Reviews in Food Science and Nutrition (2002), 42, 67-89

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Laid-Open No. 9-316252 Summary of the invention

[0011] Problems to be solved by the invention

[0012] An object of an embodiment of the present invention is to provide a water vapor barrier composition that can easily form a water vapor barrier composition layer containing an organic material on a substrate such as a plastic film or paper by coating and can exhibit higher water vapor barrier properties than conventionally known organic compositions, and a water vapor barrier laminate using the water vapor barrier composition.

[0013] Technical means of solving problems

[0014] The present inventors have conducted intensive studies to solve the above problems and, as a result, have found that water vapor barrier properties can be exhibited by allowing an organic material having a specific structure to coexist with a hydrocarbon wax, thereby completing the present invention.

[0015] That is, one embodiment relates to a water vapor barrier composition including a styrene-based thermoplastic resin (A) and a hydrocarbon wax (B).

[0016] Another embodiment relates to a water vapor barrier laminate including a substrate and a water vapor barrier composition layer obtained by applying the water vapor barrier composition on the substrate.

[0017] Effects of the Invention

[0018] According to an embodiment of the present invention, a water vapor barrier composition can be provided which can form a water vapor barrier composition layer on a substrate such as a plastic film by coating and can exhibit higher water vapor barrier properties than conventionally known organic materials, and a water vapor barrier laminate using the water vapor barrier composition. DETAILED DESCRIPTION

[0019] Hereinafter, embodiments of the present invention will be described.

[0020] According to an embodiment of the present invention, the water vapor barrier composition and the water vapor barrier laminate include a styrene-based thermoplastic resin (A) and a hydrocarbon wax (B).

[0021] <Styrene-based thermoplastic resin (A)>

[0022] The styrene-based thermoplastic resin (A) used in the embodiment of the present invention generally has a polystyrene block and a rubber middle block. The polystyrene portion forms a physical crosslink (region) and becomes a bridge point, and the middle rubber block gives the product rubber elasticity. The middle soft segment includes polybutadiene (B), isobutylene (IB), polyisoprene (I) and polyolefin elastomer (ethylene-propylene, EP), etc., which are divided into straight chain (linear type) and radial (radical type) according to the arrangement of polystyrene (S) in the hard segment. As the styrene-based thermoplastic resin (A), a styrene-based elastomer is preferred. The styrene-based elastomer may be an elastomer containing a C=C double bond, or may be a hydrogenated product thereof (i.e., a hydrogenated styrene-based elastomer). The styrene-based thermoplastic resin (A) may specifically include a styrene-isobutylene-styrene copolymer (StyreneIsobutylene Styrene, SIBS), a styrene-isoprene-styrene block copolymer (StyreneIsopreneStyrene, SIS), a styrene-ethylene-propylene-styrene block copolymer (StyreneEthylenePropyleneStyrene, SEPS), a styrene-butylene-styrene block copolymer (StyreneButyleneStyrene, SBS), a styrene-ethylene-butylene-styrene block copolymer (StyreneEthyleneButyleneStyrene, SEBS), a styrene-butadiene-isoprene-styrene block copolymer (StyreneButadieneIsopreneSyrene, SBIS), a styrene-ethylene-ethylene-propylene-styrene block copolymer (StyreneEthyleneEthylenePropyleneStyrene, SEEPS) and a styrene-butadiene copolymer (Styrene Butadiene (SB), and their acid-modified, anhydride-modified and amine-modified forms. However, it is not limited to these resins, and it is preferred that the styrene-based thermoplastic resin (A) and the hydrocarbon wax (B) are compatible in the ink when the solvent described later is added to make the ink.Among them, it is preferred that it comprises one or more selected from the group consisting of styrene-isobutylene-styrene copolymer (SIBS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-ethylene-butylene-styrene block copolymer (SEBS) and styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), and their acid-modified forms, acid anhydride-modified forms and amine-modified forms. It is more preferred that it comprises one or more selected from the group consisting of styrene-isobutylene-styrene copolymer (SIBS), styrene-ethylene-propylene-styrene block copolymer (SEPS) and styrene-ethylene-butylene-styrene block copolymer (SEBS), and their acid-modified forms, acid anhydride-modified forms and amine-modified forms. It is further preferred that it comprises one or more selected from the group consisting of styrene-isobutylene-styrene copolymer (SIBS) and styrene-ethylene-butylene-styrene block copolymer (SEBS), and their acid-modified forms, acid anhydride-modified forms and amine-modified forms.

[0023] Examples of commercially available products of such styrene-based thermoplastic resins (A) include: FG1901, FG1924, G1650, D1117, G1643, FG1924, and MD1648 manufactured by Kraton; AR-GB-40, AR-1040, AR-NF0-80B, AR-815, and AR-8050NC manufactured by Aron Chemicals; SEPTON 1020, SEPTON 2002, SEPTON 2063, and SEPTON 2064 manufactured by Kuraray. SEPTON HG-252; Asaprene T-411, Tuftec H1401, Tuftec H1517, Tuftec MP10 manufactured by Asahi Kasei; JSRSIS 5002, JSRSIS 5506 manufactured by JSR; SIBSTAR 072T, SIBSTAR 073T, SIBSTAR 102T manufactured by Kaneka Chemical, etc.

[0024] The weight average molecular weight of the styrene thermoplastic resin (A) is preferably 10,000 to 200,000, more preferably 30,000 to 170,000, and further preferably 60,000 to 130,000. When it is within the above range, water friction resistance is improved. The styrene content of the styrene thermoplastic resin (A) is preferably 5% to 65% by mass, more preferably 15% to 50% by mass, and further preferably 25% to 35% by mass in 100% by mass of the styrene thermoplastic resin (A). When it is within the above range, water vapor barrier properties are improved. When the styrene thermoplastic resin (A) is an acid-modified, anhydride-modified, and amine-modified form, the content of the acid, anhydride, and amine used for modification is preferably 0.01% to 10% by mass, more preferably 0.1% to 5% by mass, and further preferably 0.5% to 3% by mass in 100% by mass of the styrene thermoplastic resin (A). When it is within the above range, the adhesiveness is improved.

[0025] <Hydrocarbon wax (B)>

[0026] The hydrocarbon wax (B) used in the embodiment of the present invention refers to an organic substance that is mainly composed of a long-chain alkylene skeleton, is solid at room temperature, and becomes liquid after heating. Its skeleton may also contain an acid group, an ester group, a hydroxyl group, etc. By adding such a hydrocarbon wax (B) to the styrene-based thermoplastic resin (A), it is possible to exhibit high water vapor barrier properties that are not observed in the resin monomer. Here, as the performance factor of the water vapor barrier properties caused by the hydrocarbon wax (B), it is presumed as follows. That is, according to an embodiment of the present invention, after applying the water vapor barrier composition to the substrate described later, a water vapor barrier composition layer is formed through a heating and drying process, but in the heating and drying process, the hydrocarbon wax contained in the water vapor barrier composition begins to condense and form an aggregate. Furthermore, in the process of the hydrocarbon waxes gathering together, it is believed that an oriented structure or a crystalline structure derived from the high crystallinity of the hydrocarbon wax is formed on the surface. As a result, it is considered that a dense wax layer is formed in the water vapor barrier composition layer described later, especially near the interface and / or the surface, and the dissolution and diffusion of water vapor are suppressed due to the presence of a hydrophobic and highly crystalline site through which water vapor hardly permeates, thereby exhibiting excellent water vapor barrier properties.

[0027] Specific examples of hydrocarbon wax (B) include, but are not limited to, one or more of the group consisting of natural waxes such as paraffin wax, microcrystalline wax, beeswax, montan wax, ozokerite, ceresin, carnauba wax, candelilla wax, beeswax, wood wax, rice bran wax, and synthetic wax. The hydrocarbon wax (B) is preferably uniformly dissolved in the water vapor barrier composition. As commercially available products, natural waxes include paraffin wax or microcrystalline wax manufactured by Nippon Seira Co., Ltd. and ENEOS Co., Ltd. Further examples include: FT115, FT0165, SX105, and FNP0090 manufactured by Nippon Seiwa Co., Ltd.; CERAMER polymers, POLYWAX polyethylene waxes, UNICID carboxylic acids, UNILIN alcohols, UNITHOX ethoxylates, PETROLITE copolymers, and VYBAR polymers manufactured by Baker Hughes; Diacarna manufactured by Mitsubishi Chemical; and synthetic waxes such as SUNWAX series and VISCOL series manufactured by Sanyo Chemical Co., Ltd. In addition, as commercially available products, the waxes used in the examples can be cited. Furthermore, oxidized waxes produced by using these as raw materials through chemical reactions such as oxidation, saponification, esterification, maleation, and acid anhydride, blended waxes obtained by blending these waxes in resins, and emulsion waxes obtained by dispersing these waxes in water are also included in the hydrocarbon wax (B).

[0028] In order to make the hydrocarbon wax show good water vapor barrier properties, the melting point of the hydrocarbon wax is preferably 30°C or more and 80°C or less, and more preferably 40°C or more and 70°C or less. In addition, it is preferred that 80% by mass or more of the hydrocarbon wax (B) is a hydrocarbon wax (b1) having a straight-chain structure without branches, and more preferably 90% by mass or more is a hydrocarbon wax having a straight-chain structure without branches. When it is in the above range, the water vapor barrier property becomes good because the crystallinity of the hydrocarbon wax (B) is improved. In addition, as a hydrocarbon material that is solid at room temperature and has a melting point of 30°C to 80°C and shows the same properties, waxy olefins having double bonds in the molecule are also included in the hydrocarbon wax (B), and their mixtures can be listed. Among the hydrocarbon wax (B), paraffin wax and microcrystalline wax are preferred, and paraffin wax is most preferred. Because of their excellent crystallinity, they can particularly promote the formation of the wax aggregate structure in the water vapor barrier composition, and the water vapor barrier property becomes good.

[0029] When the total solid content of the water vapor barrier composition is set to 100% by mass, the content of the hydrocarbon wax (B) is preferably 5% to 80% by mass, more preferably 8% to 50% by mass, further preferably 15% to 40% by mass, and particularly preferably 20% to 30% by mass. By being within the above range, in the water vapor barrier composition as an embodiment of the present invention, the miscibility with other components is improved, and a more excellent water vapor barrier property can be exhibited in the water vapor barrier laminate. In addition, when the hydrocarbon wax (B) is a blended wax, the content of the hydrocarbon wax (B) other than the resin is preferably within the above range, and in addition, when the hydrocarbon wax (B) is an emulsion wax, the content of the hydrocarbon wax (B) other than water is preferably within the above range.

[0030] The solid content ratio (mass ratio) of the styrene-based thermoplastic resin (A) to the hydrocarbon wax (B) is preferably 9:1 to 2:8, more preferably 8.5:1.5 to 4:6, and still more preferably 8:2 to 6:4. Within the above range, water vapor barrier properties are improved.

[0031] <Solvent (C)>

[0032] The water vapor barrier composition may further include a solvent (C). In an embodiment of the present invention, as the solvent (C) used in the water vapor barrier composition, for example, as an organic solvent, methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, isobutyl acetate, propyl acetate, ethyl cellosolve acetate, n-propyl acetate, isopropyl acetate, isobutyl acetate, propylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate and other ester solvents; methanol, ethanol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-propyl alcohol, propylene glycol monoethyl ether, propylene glycol monomethyl ether and other alcohol solvents; acetone, methyl ethyl ketone, cyclohexanone and methyl isobutyl ketone and other ketone solvents; toluene, benzene, cyclohexane, hexane, methylcyclohexane, ethylcyclohexane and other hydrocarbon solvents and other well-known solvents can be used. They can also be used alone or in combination of two or more as solvent (C). The content of the organic solvent in the solvent (C) is preferably 40% by mass to 95% by mass, more preferably 50% by mass to 90% by mass, and still more preferably 60% by mass to 85% by mass.

[0033] Among these solvents (C), in order to form the aggregate structure of the hydrocarbon wax described above, it is preferred to use an organic solvent having a dispersion term δd of 14 or more and a dipole term δp of 3 or less in the water vapor barrier composition, and it is more preferred to use an organic solvent (C1) having a dispersion term δd of 15 or more and a dipole term δp of 4 or less, in terms of relatively high compatibility with the styrene-based thermoplastic resin (A) or the hydrocarbon wax (B) in the water vapor barrier composition, and good crystallization and surface migration of the wax after drying. It is further preferred to use an organic solvent (C1) having a dispersion term δd of 15 or more and a dipole term δp of 4 or less, and it is preferred that the organic solvent (C1) is contained in the solvent (C) in an amount of 50% by mass or more. Examples of the organic solvent having a dispersion term δd of 15 or more and a dipole term δp of 4 or less in the HSP value include non-polar solvents such as toluene, methylcyclohexane, cyclohexane, heptane, octane, and hexane. The HSP value is a value obtained by dividing the solubility parameter introduced by Hildebrand into three components, namely, dispersion term δd, polar term δp, and hydrogen bonding term δh, and taking into account the polarity of the substance. The HSP value can be obtained using a known value or using personal computer software HSPiP (source: http: / / www.hansen-solubility.com / index.html) or the like.

[0034] The mass of the solvent (C) when used is not particularly limited, but the content of the solvent (C) in the water vapor barrier composition is preferably 50 to 95 mass%, more preferably 65 to 90 mass%, and even more preferably 75 to 85 mass%.

[0035] When the organic solvent (C1) is used, the content of the organic solvent (C1) in the solvent (C) is preferably 50% by mass to 100% by mass, and more preferably 70% by mass to 95% by mass.

[0036] <Other ingredients>

[0037] As long as the water vapor barrier composition is within the scope of not damaging the effect of the present invention, various additives can also be appropriately formulated. For example, from the perspectives of reducing curing shrinkage, reducing thermal expansion, improving dimensional stability, improving elastic modulus, adjusting viscosity, improving strength and improving toughness, hardeners such as polyisocyanate or epoxy resin, polycarbodiimide compound or organic fillers or inorganic fillers, liquid rubber can be formulated. Such fillers can include materials such as polymers, ceramics, metals, metal oxides, metal salts and dyeing pigments. In addition, there is no particular limitation on its shape, for example, it can be particulate and fibrous. In addition, in order to adjust the leveling, coating and adhesion with the substrate, silane coupling agent, titanate coupling agent, flame retardant, storage stabilizer, antioxidant, metal passivator, ultraviolet absorber, thixotropy imparting agent, leveling agent, defoamer, dispersion stabilizer, fluidity imparting agent, defoamer and colorant can also be added. In addition, in order to improve fluidity or adhesion, liquid rubber or softener can also be included.

[0038] <Water vapor barrier composition>

[0039] In an embodiment of the present invention, the water vapor barrier composition can be obtained by mixing a styrene thermoplastic resin (A) and a hydrocarbon wax (B) and other optional components used as needed using a roller, a mixer, a melting kiln, etc., but is not particularly limited. As long as these components can be uniformly mixed, any method can be used. The water vapor barrier composition can be added with a solvent (C) as needed, but it can also be set to a non-curable resin that can flow at high temperatures and return to a non-flowable state by cooling, i.e., a so-called hot melt type. In addition, the water vapor barrier composition can also be set to a curable composition that is formed on a laminated sheet comprising a substrate or a layer other than a substrate and a water vapor barrier composition layer by admixing an arbitrary curing agent component and then subjected to a curing (crosslinking) reaction.

[0040] In addition, in an embodiment of the present invention, the water vapor barrier composition can also be obtained by uniformly mixing a styrene-based thermoplastic resin (A) with a hydrocarbon wax (B), a solvent (C), and any other components used as needed. From the perspective of imparting appropriate coating, the water vapor barrier composition can be made into ink by adding a solvent, and a layer of the water vapor barrier composition is formed on a substrate by a coating method described later. As a method for uniform mixing, a kiln or a glass bottle including a mixer such as a planetary mixer or a distributor can be used for processing, and a ball mill, a bead mill, a roller mill, a pebble mill, a grinder, a sand mill, etc. can also be applied for dispersion treatment. In addition, in the stirring and dispersing process, the styrene-based thermoplastic resin (A) or the hydrocarbon wax (B) may not be completely dissolved, and a particulate emulsion may also be formed. When bubbles or unexpected coarse particles are contained in the water vapor barrier composition, in order to reduce the quality of the coating, it is preferably removed by filtering. The filter can use a filter known in the past.

[0041] <Base material>

[0042] The substrate may include resin sheets, paper, aluminum sheets (aluminum foil), etc. For example, as resin sheets, polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate resins, polyarylate resins, acrylic resins, polyphenylene sulfide resins, polystyrene resins, vinyl resins, vinyl chloride resins, polyimide resins, epoxy resins, polyethylene, polypropylene, polyolefin resins such as polynorbornene, etc. may be included. In addition, it may be a laminated body with metals laminated on these sheets, for example, it may be a laminated body with aluminum laminated on a polyethylene terephthalate (PET) sheet. Among the substrates, polypropylene, polyethylene terephthalate, polyethylene, etc. are preferred because laminated sheets with good elongation, light transmittance, and rigidity can be obtained.

[0043] In the range that does not impair the effect of the present invention, the substrate may contain one or more arbitrary components. In the embodiment of the present invention, the substrate may also contain ultraviolet absorbers, antioxidants, antistatic agents, surfactants, pigments, and fluorescent whitening agents. The substrate may contain inorganic particles including silicon dioxide, calcium carbonate or titanium oxide, or organic particles including acrylic resin or styrene resin.

[0044] (Paper substrate)

[0045] There is no particular limitation on the paper substrate, as long as it is paper with plant-derived pulp as the main component. Specific examples of paper substrates include bleached or unbleached kraft paper, high-quality paper, cardboard, backing paper, coated paper, plain paper, glass paper, graphane paper, etc. The thickness of the paper substrate can be, for example, more than 30 μm and less than 100 μm, or more than 30 μm and less than 70 μm. In addition, the thickness of the paper substrate can be more than 70% of the overall thickness of the laminate. If the thickness of the paper substrate is more than 70% of the overall thickness of the laminate, it can be said that the environmental adaptability is excellent.

[0046] The basis weight of the paper substrate can be appropriately selected according to the desired quality and handling properties of the water vapor barrier laminate, but is usually preferably 20 g / m 2 Above and 600g / m 2 When it is a packaging material for food packaging, bags, paper containers, cardboard boxes, cups, etc., it is more preferably 25 g / m 2 Above and 600g / m 2 the following.

[0047] <Water vapor barrier laminate>

[0048] In an embodiment of the present invention, the water vapor barrier laminate has a substrate and a water vapor barrier composition layer obtained by coating the water vapor barrier composition of the embodiment on the substrate. For example, the water vapor barrier laminate has a water vapor barrier composition layer formed by coating the water vapor barrier composition on one side or both sides of the substrate. The substrate may be a resin sheet or a paper substrate. The coating method of the water vapor barrier composition also includes a printing method, and is not particularly limited, and a known coating method can be effectively used. Examples of coating methods include wire bar coating, die coating, casting, slot coating, omega coating, spiral coating, controlled seam coating, slot coating, dot coating, hot melt applicator coating, hot melt coater coating, blade coating, dip coating, gravure coating, micro gravure coating, curtain spray coating, bead coating, hot melt roller coater coating, and spin coating. Examples of printing methods include inkjet printing, spray printing, roller printing, blade roller printing, scraper printing, curtain coating printing, slit coating printing, screen printing, reverse printing, push printing, and slit coater printing. After the water vapor barrier laminate is coated on a substrate by these methods, the solvent (C) is removed, or, for the purpose of promoting crosslinking, heating or reduced pressure drying is performed as needed. The drying conditions are not particularly limited as long as the substrate is not deteriorated by the film thickness or the substrate and the selected organic solvent, and preferably, hot air heating is used at about 40°C to 200°C.

[0049] When a resin sheet is used as the substrate, the thickness of the water vapor barrier composition layer is not particularly limited, but is preferably a thin film for the purpose of suppressing cracking during bending, and is preferably 0.1 μm to 200 μm in a dry state, more preferably 0.5 μm to 10 μm, and further preferably 1.0 μm to 5.0 μm.

[0050] When a paper substrate is used as the substrate, the amount of the water vapor barrier composition applied is not particularly limited, but the larger the amount of application, the more uniformly a water vapor barrier composition layer can be formed on the paper substrate impregnated with the water vapor barrier composition, thereby exhibiting sufficient water vapor barrier performance. Therefore, when the water vapor barrier composition is directly applied on the paper substrate, the amount of the water vapor barrier composition applied in a dry state is preferably 3.5 g / m 2 ~15.0g / m 2 , more preferably 4.0 g / m 2 ~10.0g / m 2 , and more preferably 4.5g / m 2 ~8.0g / m 2 .

[0051] In addition, the water vapor barrier composition layer formed here may be laminated in one or more layers on one or both sides of the substrate. When multiple water vapor barrier composition layers are provided, their compositions may be the same or different. For example, after applying the water vapor barrier composition to one side of the substrate, a drying process may be performed, and then the same water vapor barrier composition layer may be formed in the same process to form two layers, or different water vapor barrier composition layers may be formed to form three layers.

[0052] In addition to the substrate and the water vapor barrier composition layer, the water vapor barrier laminate may also be provided with any organic layer or inorganic layer. Examples of the arbitrary layer include a heat seal layer, an adhesion coating, a printing ink layer, a top coating layer or an outer coating layer. These layers may include one or more layers. The arbitrary layer described herein is not particularly limited, and may be a layer directly formed on the substrate, or may be a layer formed by separating the water vapor barrier composition layer. For example, from the perspective of protecting the water vapor barrier composition layer or improving the wear resistance, a protective layer and an adhesive layer may also be provided on the water vapor barrier composition layer as required. In addition, the adhesion coating layer is preferably formed between the water vapor barrier composition layer and the substrate, and the top coating layer is preferably formed on the water vapor barrier composition layer formed by separating the substrate. For example, the water vapor barrier laminate has at least one layer selected from the group consisting of a heat seal layer, an adhesion coating layer, a printing ink layer and a top coating layer.

[0053] Examples of the structure of the laminate include substrate / water vapor barrier composition layer, substrate / printing ink layer / water vapor barrier composition layer, substrate / anchor coating / water vapor barrier composition layer, substrate / water vapor barrier composition layer / top coating layer, substrate / printing ink layer / anchor coating / water vapor barrier composition layer, substrate / printing ink layer / anchor coating / water vapor barrier composition layer / top coating layer, substrate / anchor coating / printing ink layer / water vapor barrier composition layer, substrate / anchor coating / printing ink layer / water vapor barrier composition layer / top coating layer, substrate / water vapor barrier composition layer / printing ink layer, substrate / water vapor barrier composition layer / printing ink layer / top coating layer, heat seal layer / substrate / water vapor barrier composition layer, heat seal layer / substrate / printing ink layer / water vapor barrier composition layer, heat seal layer / substrate / anchor coating / water vapor barrier composition layer, heat seal layer / substrate / water vapor barrier composition layer Water vapor barrier composition layer / top coating layer, heat seal layer / substrate / printing ink layer / tackifying coating layer / water vapor barrier composition layer, heat seal layer / substrate / printing ink layer / tackifying coating layer / water vapor barrier composition layer / top coating layer, heat seal layer / substrate / tackifying coating layer / printing ink layer / water vapor barrier composition layer, heat seal layer / substrate / tackifying coating layer / printing ink layer / water vapor barrier composition layer / top coating layer, heat seal layer / substrate / water vapor barrier composition layer / printing ink layer, heat seal layer / substrate / water vapor barrier composition layer / printing ink layer / top coating layer, heat seal layer / water vapor barrier composition layer / substrate, heat seal layer / water vapor barrier composition layer / substrate / printing ink layer, heat seal layer / water vapor barrier composition layer / substrate / printing ink layer / top coating layer, in terms of the physical properties of the laminate such as water vapor barrier performance or friction resistance,More preferably, it is substrate / printing ink layer / water vapor barrier composition layer, substrate / adhesion coating / water vapor barrier composition layer, substrate / water vapor barrier composition layer / top coating layer, substrate / printing ink layer / adhesion coating / water vapor barrier composition layer, substrate / printing ink layer / adhesion coating / water vapor barrier composition layer / top coating layer, substrate / adhesion coating / printing ink layer / water vapor barrier composition layer, substrate / adhesion coating / printing ink layer / water vapor barrier composition layer / top coating layer, substrate / water vapor barrier composition layer / printing ink layer / top coating layer, heat seal layer / substrate / printing ink layer / water vapor barrier composition layer, heat seal layer / substrate / adhesion coating / water vapor barrier composition layer, heat seal layer / substrate / water vapor barrier composition layer / top coating, heat seal layer / substrate / printing ink layer / tackifying coating / water vapor barrier composition layer, heat seal layer / substrate / printing ink layer / tackifying coating / water vapor barrier composition layer / top coating, heat seal layer / substrate / tackifying coating / printing ink layer / water vapor barrier composition layer, heat seal layer / substrate / tackifying coating / printing ink layer / water vapor barrier composition layer / top coating, heat seal layer / substrate / water vapor barrier composition layer / printing ink layer / top coating, heat seal layer / substrate / water vapor barrier composition layer / printing ink layer / top coating, heat seal layer / water vapor barrier composition layer / substrate, heat seal layer / water vapor barrier composition layer / substrate / printing ink layer, heat seal layer / water vapor barrier composition layer / substrate / top coating, heat seal layer / water vapor barrier composition layer / substrate / printing ink layer / top coating. ,

[0054] When a resin sheet is used as the substrate, the thickness of the laminated body when any layer is provided is not particularly limited, but is preferably 0.1 μm to 200 μm in a dry state, more preferably 0.5 μm to 10 μm, and further preferably 1.0 μm to 5.0 μm. In the case of a laminated body in which an anchor coating is formed between a paper substrate and a water vapor barrier composition layer, the amount of the water vapor barrier composition applied is not particularly limited, but is preferably 0.5 g / m 2 ~10.0g / m 2 , more preferably 1.0 g / m 2 ~7.0g / m 2 , and more preferably 1.5 g / m 2 ~6.5g / m 2 .

[0055] There is no particular limitation on the method of stacking organic or inorganic layers. For example, they may be stacked by a wet process such as coating, or they may be stacked from above by film or extrusion processing or lamination. They may also be a stack including layers formed by a vacuum process such as vapor deposition or CVD.

[0056] Examples of the material for the organic layer include polyvinyl alcohol resins, polyolefin resins (polyethylene, polypropylene, poly-4-methyl-1-pentene, polybutene, etc.), cyclic olefin resins, polyester resins (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyamide resins (nylon-6, nylon-66, poly(m-xylylene adipamide), polyacetal resins, polyacrylic acid resins, polyurethane resins, polyvinyl pyrrolidone resins, polysulfonic acid resins, starch resins, cellulose resins, polyvinyl chloride resins, polyvinyl acetate resins, polyphenylene sulfide resins, phenol resins, styrene resins, silicone resins, epoxy resins, polycarbonate resins, ionomer resins, alkyd resins, diallyl phthalate resins, melamine resins, polyacrylonitrile resins, polycaprolactone resins, polyethyleneimine resins, polyimide resins, and the like. They can be used alone or in combination. Materials for the inorganic layer include metals and semimetals such as chromium, titanium, zinc, cobalt, copper, silver, aluminum, tin, and silicon; or oxides, nitrides, oxynitrides, sulfides, and phosphides of the metals and semimetals such as silicon dioxide, aluminum oxide, titanium oxide, zinc oxide, and silicon nitride. They can be used alone or in combination.

[0057] When one or more water vapor barrier composition layers and one or more organic layers or inorganic layers are contained on one side or both sides of the substrate, the stacking order of these layers is arbitrary.

[0058] The adhesion promoter coating layer, the printing ink layer, the top coating layer or the outer coating layer may be a conventionally known layer as these layers.

[0059] <Adhesion coating>

[0060] By forming an adhesion-enhancing coating between the substrate and the water vapor barrier composition layer, the adhesion of the water vapor barrier composition layer to the substrate is improved. In addition, when a paper substrate is used as the substrate, by forming an adhesion-enhancing coating between the substrate and the water vapor barrier composition layer, the adhesion-enhancing coating acts as a filler, so even if the coating amount of the water vapor barrier composition is reduced, sufficient water vapor barrier performance can be exhibited, and the water resistance of the laminate can be improved. As an adhesion-enhancing coating agent for forming the adhesion-enhancing coating, an oily adhesion-enhancing coating agent or an aqueous adhesion-enhancing coating agent can be used. The adhesion-enhancing coating may include a polyurethane resin. In the case of a laminate in which an adhesion-enhancing coating is formed between a paper substrate and a water vapor barrier composition layer, the coating amount of the adhesion-enhancing coating agent used in the adhesion-enhancing coating is not particularly limited, and is preferably 0.5 g / m in a dry state. 2 ~10.0g / m 2 , more preferably 1.0 g / m 2 ~7.0g / m 2 , and more preferably 1.5 g / m2 ~6.5g / m 2 .

[0061] <Oil-based adhesion promoter>

[0062] Examples of binder resins used in oily adhesion-enhancing coating agents include, but are not limited to, polyurethane resins, cellulose resins, polylactic acid resins, polyamide resins, vinyl chloride-vinyl acetate copolymer resins, vinyl chloride-acrylic acid copolymer resins, rosin resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, acrylic resins, styrene resins, positive resins, styrene-maleic acid copolymer resins, polyester resins, alkyd resins, terpene resins, phenol-modified terpene resins, ketone resins, cyclized rubber, chlorinated rubber, butyral, polyacetal resins, petroleum resins and their modified resins, etc. These resins can be used alone or in combination of two or more. Polyurethane resins, cellulose resins, polylactic acid resins are preferred, and polyurethane resins are particularly preferred.

[0063] <Polyurethane resin>

[0064] The weight average molecular weight of the polyurethane resin is preferably 10,000 to 100,000, more preferably 15,000 to 70,000, and still more preferably 20,000 to 40,000. The glass transition temperature of the polyurethane resin is preferably 0°C or lower, more preferably -60°C to 0°C, and still more preferably -40°C to -5°C.

[0065] In addition, the polyurethane resin preferably has an amine value and / or a hydroxyl value (in other words, the amine value and / or the hydroxyl value is preferably greater than 0 mgKOH / g), and the amine value is preferably 0.5 mgKOH / g to 30 mgKOH / g, and more preferably 1 mgKOH / g to 20 mgKOH / g. In addition, the hydroxyl value is preferably 0.5 mgKOH / g to 30 mgKOH / g, more preferably 1 mgKOH / g to 20 mgKOH / g, and further preferably 3 mgKOH / g to 10 mgKOH / g. If it is within the above range, the adhesion to the substrate is improved. The urea bond concentration of the polyurethane resin is 0.1 mmol / g to 1.3 mmol / g, and further preferably 0.3 mmol / g to 1.15 mmol / g, and further preferably 0.6 mmol / g to 0.9 mmol / g. If it is within the above range, the adhesion to the substrate is improved. The urethane bond concentration of the polyurethane resin is preferably 0.1 mmol / g to 2.0 mmol / g, more preferably 0.2 mmol / g to 1.14 mmol / g, and still more preferably 0.4 mmol / g to 0.7 mmol / g. Within the above range, the adhesion to the substrate is improved.

[0066] (Urethane bond concentration)

[0067] The urethane bond concentration refers to a value represented by the following formula.

[0068] When (NCO mole number / OH mole number)>1 in the raw materials constituting the polyurethane resin, it is represented by the following formula 1.

[0069] Formula 1

[0070] Urethane bond concentration (mmol / g) = total hydroxyl molar number (mmol) / total solid content mass (g)

[0071] Here, the total number of moles of hydroxyl groups refers to the total number of moles of hydroxyl groups possessed by the polyol or the like used in the reaction for forming the polyurethane resin. In addition, the total solid content refers to the total mass of nonvolatile components that become the polyurethane resin.

[0072] When (NCO mole number / OH mole number) < 1, it is represented by the following formula 2.

[0073] Formula 2

[0074] Urethane bond concentration (mmol / g) = total isocyanate group molar number (mmol) / total solid content mass (g)

[0075] Here, the total number of moles of isocyanate groups refers to the total number of moles of isocyanate groups contained in the polyisocyanate used in the reaction for forming the polyurethane resin.

[0076] (Urea bond concentration)

[0077] The urea bond concentration refers to a value represented by the following formula.

[0078] After synthesizing a prepolymer having a terminal isocyanate group under the condition of (NCO mole number / OH mole number)>1, the chain is extended with a polyamine. When the polyurethane resin has an amino group at the terminal, it is represented by the following formula 3.

[0079] Formula 3

[0080] Urea bond concentration (mmol / g) = [total molar number of isocyanate groups (mmol) - total molar number of hydroxyl groups (mmol)] / total mass of solid content (g)

[0081] After synthesizing a prepolymer having a terminal isocyanate group under the condition of (NCO mole number / OH mole number)>1, the chain is extended with a polyamine. When the polyurethane resin has an isocyanate group at the terminal, it is represented by the following formula 4.

[0082] Formula 4

[0083] Urea bond concentration (mmol / g) = (total number of amino moles (mmol)) / total mass of solid content (g)

[0084] Here, the total number of moles of amino groups refers to the total number of moles of primary and / or secondary amino groups possessed by the polyamine used for reacting with the prepolymer having a terminal isocyanate group to form a urea bond.

[0085] The polyurethane resin preferably contains a structural unit derived from a polyether polyol and / or a polyester polyol, and more preferably contains a structural unit derived from a polyester polyol. In 100% by mass of the polyurethane resin solid content, the total amount of the structural unit derived from the polyether polyol and / or the polyester polyol is preferably 5% by mass to 80% by mass, more preferably 10% by mass to 60% by mass, and further preferably 10% by mass to 50% by mass. The mass ratio of the structural unit derived from the polyester polyol to the structural unit derived from the polyether polyol is preferably 100:0 to 40:60, more preferably 100:0 to 60:40, and further preferably 100:0 to 80:20. When it is within the range, the adhesion is improved.

[0086] The polyurethane resin is not particularly limited and can be suitably manufactured by a known method. Preferably, it is a polyurethane resin obtained by using a polyol and a polyisocyanate, or a polyurethane resin obtained by reacting a urethane prepolymer of a terminal isocyanate obtained by using a polyol and a polyisocyanate with a polyamine, etc. As a manufacturing method, for example, the method described in Japanese Patent Laid-Open No. 2013-256551 Gazette, etc. can be cited.

[0087] <Cellulose resin>

[0088] Examples of the cellulose resin include nitrocellulose, cellulose acetate propionate, cellulose acetate butyrate, hydroxyalkyl cellulose, and carboxyalkyl cellulose. Among them, cellulose acetate propionate, cellulose acetate butyrate, and nitrocellulose are preferred. The molecular weight is preferably 5,000 to 1,000,000, and more preferably 10,000 to 200,000, as a weight average molecular weight. The glass transition temperature is preferably 100°C to 160°C.

[0089] <Polylactic acid resin>

[0090] The so-called polylactic acid resin is a biomass plastic with polylactic acid as the main skeleton made from starch or sugar derived from plants and through chemical processes. Unlike previous plastics made from petroleum, polylactic acid resin is a biodegradable resin that is placed in a compost or soil environment with moderate moisture and temperature after use to promote hydrolysis, and then undergoes microbial decomposition (biodegradation), and finally completely decomposes into CO2 and water. Industrially, it is a polyester resin synthesized from lactide, a cyclic dimer of lactic acid, and the lactic acid is made from starch produced from corn and the like. The polylactic acid resin preferably contains 70% to 100% by mass of structural units derived from polylactic acid relative to the entire polylactic acid resin, and more preferably contains 90% to 100% by mass.

[0091] <Water-based adhesion promoter>

[0092] As the binder resin used in the aqueous tackifying coating agent, aqueous resin can be suitably used, and the so-called aqueous refers to water-soluble or emulsion state. As aqueous resin, at least one aqueous resin selected from water-soluble resin and emulsion resin can be suitably listed, and it is also possible to mix. As the example of aqueous resin, it can be suitably listed: aqueous polyurethane resin, aqueous acrylic acid modified urethane resin, aqueous acrylic acid modified urethane urea resin, aqueous acrylic resin, aqueous styrene-acrylic acid copolymer resin, aqueous styrene-maleic acid copolymer resin, aqueous ethylene-acrylic acid copolymer resin, aqueous polyester resin, aqueous shellac, aqueous rosin modified maleic acid resin, aqueous vinyl chloride-vinyl acetate copolymer resin, aqueous vinyl chloride-acrylic acid copolymer resin, aqueous chlorinated polypropylene resin, aqueous hydroxyethyl cellulose resin, aqueous hydroxypropyl cellulose resin, aqueous butyral resin, etc. These resins can be used alone or in combination of two or more.

[0093] Among them, it is preferred to include at least one aqueous resin selected from aqueous polyurethane resin, aqueous acrylic resin, aqueous styrene-acrylic acid copolymer resin, and aqueous styrene-maleic acid copolymer resin. They preferably include 50% by mass or more, more preferably 70% by mass or more, and further preferably 80% by mass or more in the total mass of the binder resin. It is particularly preferred to include aqueous polyurethane resin.

[0094] (Waterborne polyurethane resin)

[0095] From the viewpoint of adhesion to the substrate or pigment dispersibility, the binder resin preferably comprises an aqueous polyurethane resin. The aqueous polyurethane resin has a neutralized acid value, and the acid value is preferably 20 mgKOH / g to 65 mgKOH / g. In addition, the glass transition temperature is preferably -30°C to 0°C. Here, the so-called glass transition temperature refers to the maximum value of Tanδ in the dynamic viscoelasticity measurement. As a hydroxyl value, it is preferably 1 mgKOH / g to 15 mgKOH / g.

[0096] The aqueous polyurethane resin is preferably in the following forms: a polyurethane resin synthesized from a polyol, a hydroxy acid and a polyisocyanate; or a polyurethane resin synthesized from a polyol, a hydroxy acid and a polyisocyanate, comprising a urethane prepolymer having an isocyanate group at the end and a polyurethane urea chain-extended by a polyamine.

[0097] <Water vapor permeability>

[0098] The water vapor permeability varies depending on the type of resin or the amount of wax blended. When a resin sheet is used as the substrate of a water vapor barrier laminate, the preferred range is less than 10.0 g / m2 in terms of the value of the water vapor barrier composition layer alone. 2 ·day, more preferably less than 1.0 g / m 2 When a paper substrate is used as the substrate of the water vapor barrier laminate, the preferred range is less than 200.0 g / m 2 ·day, more preferably less than 100.0g / m 2 ·sky.

[0099] In addition, the detailed measurement method of water vapor permeability is described in detail in Examples.

[0100] <Example of embodiment>

[0101] Examples of embodiments of the present invention are given below. The embodiments of the present invention are not limited to the following examples.

[0102] (1) A water vapor barrier composition comprising a styrene-based thermoplastic resin (A) and a hydrocarbon wax (B).

[0103] (2) The water vapor barrier composition according to (1) above, wherein the content of the hydrocarbon wax (B) is 5% by mass to 80% by mass based on 100% by mass of the solid content of the water vapor barrier composition.

[0104] (3) The water vapor barrier composition according to (1) or (2), wherein the styrene-based thermoplastic resin (A) comprises one or more selected from the group consisting of styrene-isoprene-styrene block copolymers (SIS), styrene-isobutylene-styrene (SIBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-butylene-styrene block copolymers (SBS), styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-butadiene-isoprene-styrene block copolymers (SBIS), styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), and styrene-butadiene copolymers (SB), and acid-modified forms thereof, acid anhydride-modified forms thereof, and amine-modified forms thereof.

[0105] (4) The water vapor barrier composition according to any one of (1) to (3), wherein the melting point of the hydrocarbon wax (B) is 30°C to 80°C, and the hydrocarbon wax (B) contains 80% by mass or more of a hydrocarbon wax (b1) having a straight chain structure without branches.

[0106] (5) The water vapor barrier composition according to any one of (1) to (4), further comprising a solvent (C).

[0107] (6) A water vapor barrier laminate comprising a substrate and a water vapor barrier composition layer obtained by applying the water vapor barrier composition according to any one of (1) to (5) above onto the substrate.

[0108] (7) The water vapor barrier laminate according to (6), wherein the substrate is a resin sheet or a paper substrate.

[0109] (8) The water vapor barrier laminate according to (6) or (7) above, further comprising at least one layer selected from the group consisting of a heat seal layer, an adhesion promoter layer, a printing ink layer, and a top coat layer.

[0110] (9) The water vapor barrier laminate according to any one of (6) to (8), wherein the anchor coating layer comprises a polyurethane resin.

[0111] The disclosed content of this application is related to the subject matter described in Japanese Patent Application No. 2021-207559 filed on December 21, 2021 and Japanese Patent Application No. 2022-079805 filed on May 13, 2022, and all of their disclosed contents are incorporated into this application by reference.

[0112] Example

[0113] Hereinafter, the present invention will be specifically and in detail described by way of examples, but these examples are only one aspect of the present invention and the present invention is not limited to these examples. In addition, in the table, "part" means "part by mass" and "%" means "% by mass".

[0114] The abbreviations of the styrene-based thermoplastic resin (A), hydrocarbon wax (B), solvent (C), other components and constituent elements described in the Examples described below and Table 1 are as follows.

[0115] <Styrene-based thermoplastic resin (A)>

[0116] A-1: Kraton Co., Ltd. Trade name: G1650 (styrene-ethylene-butylene-styrene block copolymer, styrene content 29% by mass, weight average molecular weight 109,000)

[0117] A-2: Kraton Co., Ltd. Trade name: FG1924 (maleic anhydride-modified styrene-ethylene-butylene-styrene block copolymer, styrene content 13% by mass, maleic anhydride content 1% by mass)

[0118] A-3: Kuraray Co., Ltd. Trade name: SEPTON 2063 (styrene-ethylene-propylene-styrene block copolymer, styrene content 13% by mass, weight average molecular weight 120,000)

[0119] A-4: Kaneka Chemical Co., Ltd. Trade name: SIBSTAR 073T (styrene-isobutylene-styrene block copolymer, styrene content 30% by mass, weight average molecular weight 70,000)

[0120] <Hydrocarbon wax (B)>

[0121] ·B-1: Nippon Seira Co., Ltd. Trade name: Paraffin Wax 115 (melting point: 48°C, content of straight chain structure components: 91% or more)

[0122] · B-2: Nippon Seira Co., Ltd. Trade name: Paraffin Wax 135 (melting point: 59°C, content of linear structural components: 92% or more)

[0123] · B-3: Nippon Seira Co., Ltd. Trade name: Paraffin Wax 155 (melting point: 69°C, content of straight chain structural components: 90% or more)

[0124] · B-4: Nippon Seira Co., Ltd. Trade name: Hi-Mic 2065 (melting point: 75°C, content of straight chain structural components: 81% or more)

[0125] ·B-5: Nippon Seira Co., Ltd. Trade name: Hi-Mic 2045 (melting point: 72°C, content of straight chain structural components: 80% or more)

[0126] <Solvent (C)>

[0127] C-1: Toluene (δd: 18.0, δp: 1.4)

[0128] ·C-2: MCH (methyl cyclohexane) (δd: 16.0, δp: 0)

[0129] ·C-3: Isobutyl acetate (δd: 15.1, δp: 3.7)

[0130] C-4: Butyl acetate (δd: 15.8, δp: 3.7)

[0131] C-5: Toluene / isobutyl acetate = 1 / 1 (mass ratio) (δd: 16.6, δp: 2.6)

[0132] C-6: MCH / butyl acetate = 1 / 1 (mass ratio) (δd: 15.9, δp: 1.9)

[0133] <Resin sheets (D-1) to (D-3), laminated sheets (D-4), and laminated sheets (D-5)>

[0134] ·D-1: Toray Co., Ltd. Trade name: Lumirror S10 (100 μm PET film)

[0135] ·D-2: Futamura Chemical Co., Ltd. Trade name: FOH (30μm oriented polypropylene (OPP) film)

[0136] ·D-3: Toyobo Co., Ltd. Trade name: E5102 (25μm PET film)

[0137] D-4: A laminated sheet obtained by applying gravure ink (Toyo Ink Co., Ltd. trade name: Real NEX 39 Blue BO S3) on D-1 (Lumirror S10)

[0138] D-5: A laminated sheet obtained by applying gravure ink (Toyo Ink Co., Ltd. trade name: Real NEX 39 Blue BO S3) on D-2 (FOH)

[0139] <Paper base material (D-6), Paper base material (D-7)>

[0140] ·D-6: Daio Paper Co., Ltd. Trade name: Nagoya Sunryo (single gloss paper weighing 70g)

[0141] ·D-7: Nippon Paper Manufacturing Co., Ltd. Trade name: npi high quality (high quality paper weighing 64g)

[0142] <Other ingredients (E)>

[0143] ·E-1: Idemitsu Kosan Co., Ltd. Trade name: Diana Process Oil PW90 (softener)

[0144] E-2: BASF JAPAN Co., Ltd. Trade name: IRGANOX 1010 (antioxidant)

[0145] E-3: Poly(vinylacetate) from Sigma-Aldrich

[0146] ·E-4: Daiichi Industrial Pharmaceutical Co., Ltd. Trade name: PLYSURF A212 (heat resistance enhancer)

[0147] · E-5: Mizusawa Chemical Industry Co., Ltd. Trade name: Mizukasil P707 (adhesion enhancer)

[0148] <Adhesion coating agent (F)>

[0149] F-1: Oily urethane-based (BPU410) anchor coating agent of Production Example 1

[0150] · F-2: Oily polylactic acid (PLA)-based adhesion promoter coating agent of Preparation Example 2

[0151] ·F-3: Oily cellulose-based anchor coating agent (NV: 30%, nitrogen content: 11.5% to 12.2%, weight average molecular weight: 28,000 to 33,000)

[0152] ·F-4: Aqueous urethane-based (JW303) adhesion promoter coating agent of Preparation Example 3

[0153] <Production Example 1: Method for producing oily urethane anchor coating agent F-1>

[0154] (Synthesis of urethane resin)

[0155] In a four-necked flask including a stirrer, a thermometer, a reflux cooler and a nitrogen inlet tube, 24.3 parts of a polyester polyol having a number average molecular weight of 2,000 obtained by polycondensation of biomass sebacic acid / adipic acid = 50 / 50 (mass ratio) and 1,3-propylene glycol / neopentyl glycol = 50 / 50 (mass ratio), 4 parts of isophorone diisocyanate, and 10 parts of ethyl acetate were added, and the mixture was reacted at 120° C. for 6 hours under a nitrogen flow, and 14 parts of propyl acetate was added and cooled to obtain a solution of a terminal isocyanate prepolymer. Next, the obtained solution of the terminal isocyanate prepolymer was gradually added to a mixture of 1.7 parts of isophorone diamine (hereinafter also referred to as IPDA), 18 parts of ethyl acetate and 28 parts of isopropyl alcohol (hereinafter also referred to as IPA) at room temperature, followed by reaction at 50°C for 1 hour to obtain a urethane resin solution having a solid content of 30%, a weight average molecular weight of 70,000, an amine value of 5 mgKOH / g, a urea bond concentration of 0.67 mmol / g, and a urethane bond concentration of 0.54 mmol / g.

[0156] (Manufacture of oily urethane-based anchor coating agent)

[0157] 20 parts of urethane resin solution, 10 parts of vinyl chloride-vinyl acetate resin solution, and silica particles (average particle size 5 μm, Brunauer-Emmett-Teller (BET) specific surface area 200 m 2 / g) 1 part, mixed solvent (propyl acetate (n-propyl acetate (NPAC)) / IPA = 70 / 30 (mass ratio)) 26 parts were stirred and mixed, and after grinding with a sand mill, 20 parts of urethane resin solution, 19.7 parts of mixed solvent (propyl acetate / IPA = 70 / 30 (mass ratio)), 0.1 part of polyalkyl vinyl ether (polyvinyl butyl ether copolymer number average molecular weight 5,000 solid content 20%), 3.0 parts of water, and 0.2 parts of quaternary ammonium salt (lauryltrimethylammonium chloride solid content 50%) were stirred and mixed to obtain an oily urethane-based adhesion promoter coating agent.

[0158] <Production Example 2: Production method of oily PLA-based anchor coating agent F-2>

[0159] (Synthesis of polylactic acid resin)

[0160] 100 parts of M-lactide and 0.1 parts of octanol were placed in a four-necked flask including a stirrer, a thermometer, a reflux cooler and a nitrogen inlet tube, and 0.05 parts of tin 2-ethylhexanoate were added after reaching 180° C., and after 2 hours of ring-opening polymerization, 0.08 parts of 116% strong phosphoric acid were added, and residual lactide was removed under reduced pressure. The resulting substance was adjusted to a solid content of 50% using ethyl acetate to obtain a polylactic acid resin solution with a weight average molecular weight of 50,000.

[0161] (Manufacture of oily PLA-based adhesion-enhancing coating agent)

[0162] 33.3 parts of nitrocellulose (NV.30%, nitrogen content of 11.5% to 12.2%, weight average molecular weight of 28,000 to 33,000), 39.9 parts of ethyl acetate, 20.0 parts of polylactic acid resin solution (NV.50%), 0.9 part of ORGATIX TC-100 (titanium chelate manufactured by Matsumoto Fine Chemical Co., Ltd. NV.75%), 2.0 parts of diethylene glycol monobutyl ether, and 3.9 parts of SUNWAX 131P (polyethylene wax NV.40%) were stirred and mixed to obtain an oily PLA-based adhesion promoter coating agent.

[0163] <Production Example 3: Method for producing aqueous urethane anchor coating agent F-4>

[0164] (Synthesis of urethane resin)

[0165] While introducing nitrogen into a reactor equipped with a thermometer, a stirrer, a reflux cooling tube and a nitrogen inlet tube, 96.89 parts of poly(3-methyl-1,5-pentane adipate) diol with a number average molecular weight of 400, 24.18 parts of polyethylene glycol with a number average molecular weight of 2000, 21.56 parts of 2,2-dimethylol propionic acid and 138.24 parts of isophorone diisocyanate were subjected to a boiling point reaction in 200 parts of methyl ethyl ketone for 6 hours to prepare a terminal isocyanate prepolymer, and then 100 parts of acetone were added after cooling to 40°C to obtain a solvent solution of the terminal isocyanate prepolymer. Subsequently, 580.87 parts of the obtained terminal isocyanate prepolymer solution was gradually added to a mixture of 14.35 parts of 2-hydroxyethylethylenediamine, 4.78 parts of isophoronediamine and 400 parts of acetone at room temperature, and reacted at 50°C for 3 hours to obtain a solvent-type polyurethane resin solution. Next, 9.76 parts of 28% ammonia water and 700 parts of deionized water were gradually added to the solvent-based polyurethane resin solution and neutralized to thereby dissolve in water, and then the total amount of methyl ethyl ketone and acetone was distilled off under azeotropic conditions, and then water was added to adjust the viscosity to obtain a polyurethane resin having an acid value of 30 mgKOH / g, a solid content of 30%, a viscosity of 780 mPa·s, a weight average molecular weight of 22,000, a urea bond concentration of 0.87 mmol / g, and a carbamate bond concentration of 1.79 mmol / g.

[0166] (Manufacture of water-based urethane-based adhesion promoter coating agent)

[0167] 30.00 parts of a polyurethane resin, 0.10 parts of a defoaming agent, 10.00 parts of isopropyl alcohol, and 29.90 parts of water were stirred and mixed, and after grinding with a sand mill, 20.00 parts of a polyurethane resin solution (PU01), 5.00 parts of isopropyl alcohol, and 10.00 parts of water were stirred and mixed to obtain an aqueous urethane-based anchor coating agent.

[0168] [Preparation of water vapor barrier coating agent and production of water vapor barrier sheet]

[0169] <1. Example using a resin sheet>

[0170] <Example 1>

[0171] 75 parts of styrene-based thermoplastic resin (A-1) (copolymer), 25 parts of hydrocarbon wax (B-1), and 400 parts of solvent (C-1) were added to a glass bottle and compatibilized to obtain a water vapor barrier composition. The prepared water vapor barrier composition was applied to a substrate (D-1) using a bar coater or an applicator, and dried in a hot air oven at 70°C for 5 minutes to obtain a water vapor barrier laminate. The thickness of the water vapor barrier composition layer in the dried water vapor barrier laminate was 3.0 μm.

[0172] Next, the following tests were performed using the obtained laminate. The results are shown in Table 1.

[0173] <Measurement of water vapor transmission rate>

[0174] The water vapor barrier properties of the resin sheet were evaluated by using a water vapor permeability measuring device (Permatran manufactured by MOCON) at a permeation area of ​​50 cm. 2 The water vapor permeability was measured under the conditions of 40°C, 100% humidity (saturated water vapor pressure), and 10 sccm nitrogen flow rate. The contribution of the water vapor permeability of the substrate was removed from the obtained water vapor permeability, and the water vapor permeability of the water vapor barrier composition layer alone was calculated and evaluated according to the following four stages.

[0175] A (good): water vapor permeability is less than 1.0g / (m 2 ·sky)

[0176] B (acceptable): water vapor permeability is 1.0g / (m 2 ·day) and less than 5.0g / (m 2 ·sky)

[0177] C (acceptable): water vapor permeability is 5.0 g / (m 2 ·day) and less than 10.0g / (m 2 ·sky)

[0178] D (bad): water vapor permeability is 10.0 g / (m 2 · days) or more

[0179] <Measurement of Adhesion>

[0180] In the laminated body produced, a cellophane tape (made by Nichiban, width 12 mm) was applied by rubbing the thumb 5 times on the surface on the opposite side of the substrate. The cellophane tape was pulled off the laminated body 3 times, and the adhesion to the substrate was visually evaluated. The judgment criteria are as follows.

[0181] A (good): The coating agent (water vapor barrier composition layer) was not peeled off even after rapid stretching three times.

[0182] B (acceptable): The coating agent is peeled off once or more and less than three times by rapid stretching.

[0183] C (acceptable): The coating agent peeled off three times when stretched suddenly, and did not peel off three times when stretched gradually.

[0184] D (bad): The coating agent peeled off three times when stretched suddenly, and peeled off three times when stretched gradually.

[0185] <Evaluation of Haze>

[0186] The prepared laminate was measured for TT (total light transmittance) and Dif. (diffuse transmittance) using a haze meter (manufactured by Nippon Denshoku Industries, trade name: SH7000), and evaluated based on three-level criteria using the calculated values ​​of the following formulas.

[0187] Haze = Dif. / TT

[0188] A (good): 1 or more and less than 10

[0189] B (OK): 10 or more and less than 15

[0190] C (OK): 15 or above

[0191] <Example 2 to Example 66, Comparative Example 1>

[0192] As shown in Table 1, except for changing the raw material type and blending amount of the water vapor barrier composition and the base material type of the water vapor barrier laminate, the water vapor barrier composition was prepared and the water vapor barrier laminate using the resin sheet was produced in the same manner as in Example 1, and the water vapor barrier properties, adhesion, and haze were evaluated. The results are shown in Table 1.

[0193] [Table 1]

[0194]

[0195]

[0196] <2. Example using paper substrate>

[0197] <Example 67>

[0198] 70 parts of copolymer (A-1), 30 parts of hydrocarbon wax (B-1), and 400 parts of solvent (C-1) were added to a glass bottle and compatibilized to obtain a water vapor barrier composition. The prepared water vapor barrier composition was applied to a substrate (D-6) using a bar coater or an applicator, and dried in a hot air oven at 70°C for 5 minutes to obtain a water vapor barrier laminate. The thickness of the water vapor barrier composition layer in the dried water vapor barrier laminate was 5.1 μm.

[0199] Next, the following tests were performed using the obtained laminate. The results are shown in Table 2.

[0200] <Measurement of water vapor transmission rate>

[0201] The water vapor barrier property of the paper substrate was evaluated in accordance with Japanese Industrial Standards (JIS) Z0208:1976 (cup method) B method (temperature 40°C ± 0.5°C, relative humidity 90% ± 2%). The paper substrate was arranged so that it was on the inside (low humidity side), and the water vapor barrier composition was applied. The water vapor permeability of the formed laminate was measured and evaluated according to the following four stages.

[0202] A (good): water vapor permeability is less than 100.0 g / (m 2 ·sky)

[0203] B (acceptable): water vapor permeability is 100.0 g / (m 2 ·day) and less than 150.0g / (m 2 ·sky)

[0204] C (acceptable): water vapor permeability is 150.0 g / (m 2 ·day) and less than 200.0g / (m 2 ·sky)

[0205] D (bad): water vapor permeability is 200.0 g / (m 2 · days) or more

[0206] <Measurement of Adhesion>

[0207] The produced laminate was subjected to a peel test using a cellophane tape, and the adhesion was visually evaluated. The evaluation criteria are as follows.

[0208] A (good): There is no peeling (peeling) of the coating agent.

[0209] B (acceptable): The peeling of the coating agent is less than 5%.

[0210] C (acceptable): The peeling of the coating agent is 5% or more and less than 20%.

[0211] D (bad): The coating agent peeled off by 20% or more.

[0212] <Evaluation of water resistance>

[0213] The laminated body produced was cut into a size of 17 cm × 1.5 cm and used as a test piece. A friction piece with water-containing cotton (muslin cloth No. 3) was placed on the test piece using a Gakushin friction tester (manufactured by Yasuda Seiki Seisakusho). A load of 200 g was applied to the friction piece, and the friction piece was reciprocated 100 times in the horizontal direction at a certain speed. The water resistance was evaluated by the number of reciprocations until the paper substrate was damaged. The judgment criteria are as follows.

[0214] A (good): The paper substrate was not damaged during 100 reciprocating motions.

[0215] B (acceptable): The paper substrate was damaged during 75 or more and less than 100 reciprocating movements.

[0216] C (acceptable): The paper substrate was damaged during 50 or more and less than 75 reciprocating movements.

[0217] D (bad): The paper substrate was damaged in less than 50 reciprocating motions.

[0218] <Example 68 to Example 100, Comparative Example 2>

[0219] As shown in Table 2, except for changing the raw material type and blending amount of the water vapor barrier composition and the substrate type of the water vapor barrier laminate, the water vapor barrier composition and the water vapor barrier laminate using the paper substrate were prepared in the same manner as in Example 67, and the water vapor barrier properties, adhesion, and water resistance were evaluated. In addition, in Examples 92 to 100, an anchor coating was provided. The results are shown in Table 2.

[0220]

[0221]

Claims

1. A water vapor barrier composition comprising a styrene-based thermoplastic resin (A) and a hydrocarbon wax (B).

2. The water vapor barrier composition according to claim 1, wherein The content of the hydrocarbon wax (B) is 5% by mass to 80% by mass based on 100% by mass of the solid content of the water vapor barrier composition.

3. The water vapor barrier composition according to claim 1 or 2, wherein The styrene-based thermoplastic resin (A) comprises one or more selected from the group consisting of styrene-isoprene-styrene block copolymers (SIS), styrene-isobutylene-styrene (SIBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-butylene-styrene block copolymers (SBS), styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-butadiene-isoprene-styrene block copolymers (SBIS), styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS) and styrene-butadiene copolymers (SB), and their acid-modified, anhydride-modified and amine-modified forms.

4. The water vapor barrier composition according to claim 1 or 2, wherein The melting point of the hydrocarbon wax (B) is 30° C. to 80° C., and the hydrocarbon wax (B) contains 80% by mass or more of a hydrocarbon wax (b1) having a linear structure without branches. 5 . The water vapor barrier composition according to claim 1 , further comprising a solvent (C). 6 . A water vapor barrier laminate comprising a substrate and a water vapor barrier composition layer obtained by coating the water vapor barrier composition according to claim 1 or 2 on the substrate.

7. The water vapor barrier laminate according to claim 6, wherein The substrate is a resin sheet or a paper substrate.

8. The water vapor barrier laminate according to claim 6, further comprising at least one layer selected from the group consisting of a heat seal layer, an adhesion promoter coating layer, a printing ink layer and a top coating layer.

9. The water vapor barrier laminate according to claim 8, wherein The adhesion promoting coating comprises a polyurethane resin.

Citation Information

Patent Citations

  • Water-dispersible hot melt composition, moistureproof paper using the same and their production

    JP1997316252A

  • Gravure ink composition for front printing

    JP2013256551A

  • Lid opening / closing device

    JP2022079805A